Weeds of Wheat in Nepal: A Literature Review - Dangol, Dharma Raj (Journal of Natural History Museum, 2015)
This paper reviews publications dealing with weeds and/or their control in wheat (Triticum aestivum L.) in Nepal and enumerates 370 weed species of 210 genera in 54 families. This review shows that the Asteraceae (69 spp.), Poaceae (52 spp.), Leguminosae (25 spp.), Polygonaceae (19 spp.), Caryophyllaceae (18 spp.), Scrophulariaceae (17 spp.), Euphorbiaceae and Lamiaceae (14 spp. each), Brassicaceae and Cyperaceae (13 spp.), and Solanaceae (11 spp. each) were the dominant families, which accounted for 71.35% of the total weeds. This paper also documented 63 species reported as the principal or most common weeds and 4 species (Chenopodium album, Cynodon dactylon, Phalaris minor, Polygonum plebeium) as the most commonly reported weeds of wheat in Nepal in the papers reviewed. This paper also highlighted the fact that the researchers from the Tribhuvan University, Department of Plant Resources (then Department of Medicinal Plants/HMG) and Nepal Agricultural Research Council mentioned about the deposition of their herbarium specimens in the respective organizations. This paper also analyzed the publication media in which the reviewed papers appeared.J. Nat. Hist. Mus. Vol. 27, 2013: 132-178